Effect of C-terminus site-directed mutations on the toxicity and sensitivity of Bacillus thuringiensis Vip3Aa11 protein against three lepidopteran pests. Issue 12 (2nd December 2017) - Chi, Baoyan; Luo, Guoxing; Zhang, Jinbo; Sha, Junxue; Liu, Rongmei; Li, Haitao; Gao, Jiguo
ABSTRACT: The insecticidal activities and specificities of the Vip3Aa proteins derived from different Bt strains are very different, although the similarities between these proteins are higher than 95%. In this study, we hypothesised that the differences in Vip3Aa11 and Vip3Aa39 C-terminal amino acids determine their differences in insecticidal activity against three Lepidoptera insects. To find the amino acid residues associated with insecticidal activity, nine different amino acid residues of Vip3Aa11 were substituted with the corresponding amino acid residues from Vip3Aa39 by site-directed mutagenesis. The toxicity of each protein was estimated by bioassays, and the results demonstrated that the mutant Y784N lost its insecticidal activity against three insects ( Agrotis ipsilon, Helicoverpa armigera, and Spodoptera exigua ). The insecticidal activity of S543N, I544L, and S686R against S. exigua increased 5-fold, 2.65-fold, and 8.98-fold, while the toxicity to H. armigera and A. ipsilon slightly decreased compared with that of the Vip3Aa11 protein. These findings indicate that the amino acid residues Ser 543, Ile 544, Thr 685, Ser 686, Arg 704, Ile 780, and Tyr 784 may be insecticidal activity-related residues. Additionally, the trypsin activation of the four mutants indicated that all proteins can form a 62-kDa core fragment, except Y784N. A possible association between the insecticidal activity and trypsin sensitivity of Vip3A proteins is suggested.